Comparative in-silico analysis of microbial dysbiosis discern potential metabolic link in neurodegenerative diseases - Chauhan, Vipin; Chauhan, Nitin K.; Dutta, Somit; Pathak, Dhruv; Nongthomba, Upendra (Frontiers in Neuroscience, 2023)
A healthy gut flora contains a diverse and stable commensal group of microorganisms, whereas, in disease conditions, there is a shift towards pathogenic microbes, termed microbial dysbiosis. Many studies associate microbial dysbiosis with neurodegenerative diseases, including Alzheimer's disease (AD), Parkinson's disease (PD), Multiple sclerosis (MS), and Amyotrophic lateral sclerosis (ALS). Although, an overall comparative analysis of microbes and their metabolic involvement in these diseases is still lacking. In this study, we have performed a comparative analysis of microbial composition changes occurring in these four diseases. Our research showed a high resemblance of microbial dysbiosis signatures between AD, PD and MS. However, ALS appeared dissimilar. The most common population of microbes to show an increase belonged to the phyla, Bacteroidetes, Actinobacteria, Proteobacteria and Firmicutes. Although, Bacteroidetes and Firmicutes were the only phyla that showed a decrease in their population. The functional analysis of these dysbiotic microbes showed several potential metabolic links which can be involved in the altered microbiome-gut-brain axis in neurodegenerative diseases. For instance, microbes with elevated populations lack pathways for synthesising SCFA acetate and butyrate. Also, these microbes have a high capacity for producing L-glutamate, an excitatory neurotransmitter and precursor of GABA. Contrastingly, Tryptophan and histamine have a lower representation in the annotated genome of elevated microbes. Finally, the neuroprotective compound spermidine was less represented in elevated microbes' genomes. Our study provides a comprehensive catalogue of potential dysbiotic microbes and their metabolic involvement in neurodegenerative disorders, including AD, PD, MS and ALS.